Gambaran Kejadian Obesitas pada Remaja di Pondok Pesantren Al Hidayah Kota Jambi - Rahmawati, Helfi; Fatmawati, Tina Yuli; Jeki, Andicha Gustra (3031-8572, 2024)
Obesity is an excessive accumulation of fat due to an imbalance in energy intake with energy expenditure over a long period of time. The results of the 2018 Riskesdas showed that there was an increase in the prevalence of obesity in those aged 18 years and over, from 14.8% to 21.8%. In the obese population, the prevalence was higher in women (29.3%) than in men (14.5%). Many degenerative diseases can occur in someone who is overweight such as diabetes mellitus, hypertension (high blood pressure), coronary heart disease, arthritis, and cancer. This study is a descriptive study conducted to see the picture of each variable studied at the same time. This study aims to see the picture of obesity in adolescents at the Al Hidayah Islamic Boarding School in Jambi City. This study took place at the Al Hidayah Islamic Boarding School in Jambi City. A sample of 101 people was taken by proportional random sampling. The results of the study showed that the age of the respondents was mostly 16 and 17 years old, as many as 33 people (32.67%), the majority of respondents were female, as many as 77 respondents (76.23%), the majority of respondents were in grade XII, as many as 41.58%. The description of the respondents was mostly not obese/normal, as many as 85.15%. For teenagers at the Al Hidayah Islamic Boarding School, to increase awareness of the importance of physical activity and consuming healthy and balanced nutritious food so that good nutritional status is achieve